Rehabilitation Of Geopolymer Reinforced Concrete I-Section Beams by Fiber Reinforced Polymer Bottom Strips (Eurasian Journal of Engineering and Technology, 2023)
The key factor contributing to global warming is the huge CO2 emissions that can be related to the production of cement. Thus, Finding long-term answers to this issue is therefore driven by a variety of motivations for both the writers and research groups. When certain source materials, such as fly ash, metakaoline, rice husk ash, and crushed granulated blast furnace slag are alkali activated, the resulting principal binder is what is known as geopolymer concrete. Commonly, geopolymer concrete has mechanical strength characteristics similar to those of traditional concrete. Repairing RC beams refers to the actions that can be done in order to recover the inherent structural behavior before failure. This study was devoted to examine feasibility of using bottom strips technique that made by fiber reinforced polymers to repair pre-failed I – section reinforced geopolymer beams. Both Glass and Carbon fiber reinforced polymer strips were used and compared. The results showed that the proposed technique was able to recover the service load and the maximum load. The stiffness levels was increased after rehabilitation for both glass and carbon fiber. The initial cracking load occurrence was changed in nature from the tension to compression zone after repairing.